Analisis Kemampuan Membaca Lancar Siswa Kelas 1 di Sekolah Dasar - Indah Insani Rambe; Chandra Chandra; Inggria Kharisma (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Fluent reading ability level 1 in elementary school is the initial stage in the fluent reading process, which focuses on basic reading skills such as recognizing letters, words, and simple sentences. Elementary school students at this level are expected to be able to read fluently and accurately, and understand the meaning of the text being read. Fluent reading ability level 1 is an essential aspect in learning activities at the elementary school level, because it can affect children's ability to master other learning content. Thus, teachers and parents need to pay attention to and improve elementary school students' fluent reading ability level 1 through effective learning strategies and techniques..